Help-Seeking Behaviors and Related Factors in Chinese Patients With Major Depressive Disorder: A Community-Based Cross-Sectional Study - Cui, Xiaojuan; Li, Minghui; Li, Peijun; Li, Jinhao; Hou, Xiaofei; Yan, Guoli; Li, Peiyao; Su, Xuyang; Qin, Danni; Zhang, Yijiao; Gu, Yan; Yin, Huifang; et al. (Frontiers in Psychiatry, 2022)
Background: Although evidence-based and effective treatments are available for people with Major depressive disorder (MDD), a substantial number do not seek or receive help. Therefore, this study aimed to (1) investigate the total help-seeking rate and first-time help-seeking choices; (2) explore the perceived helpfulness on 23 potential sources and (3) evaluate the factors related to help-seeking behaviors among patients with MDD. Methods: Data came from the Tianjin Mental Health Survey (TJMHS), which included a representative sample of adult community residents (n=11,748) in the Chinese municipality of Tianjin. Of these, 439 individuals were diagnosed with lifetime MDD according to the Diagnostic and Statistical Manual-fourth edition (DSM-Ⅳ) and administered a Help-Seeking Questionnaire. Results: 28.2% of patients with MDD living community reported that they had ever sought any help during their entire lifetime before the interview, with 8.2% seeking help in mental healthcare settings, 8.0% only in other healthcare settings and 12.0% only in non-healthcare sources (e.g., family, friends, and spiritual advisor). Among help-seekers, the first help mainly was sought in non-healthcare sources (61.3%), followed by healthcare settings (25.8%) and mental healthcare settings (12.9%). The majority of MDD individuals thought the non-healthcare sources were not helpful and mental healthcare settings were helpful or possibly helpful to solve mental problems. Female, having 10-12 or higher education years, comorbid anxiety disorders were associated with increased help-seeking. Conclusion: A small percentage of individuals with MDD living in community of Tianjin sought help. They preferred non-healthcare sources to healthcare settings. Demographic and clinical features were associated with help-seeking behaviors.